Muscular ventricular septal defect closure with Gianturco coil at Soetomo hospital (a case report) - Alit Utamayasa; Teddy Ontoseno; Mahrus A Rahman; Vinny Yoanna; Rio Herdyanto (Paediatrica Indonesiana, 2010)
Ventricular septal defect (VSD) is the mostcommon congenital heart disease (CHD)in children.1'2 It occurs in 1.5 to 3.5 of1,000 live births and constitutes 20% ofcongenital cardiac defects.1 The VSD may be small,medium or large and is classified based on its locationin the interventricular septum. There are four types ofVSD, i.e., perimembranous (80% ofVSDs), musculartype (5% to 20%) inlet or AV canal type (8%), andfinally, subpulmonary (5% to 7%).1-4 When multiplemuscular defects are seen, it is often referred to as"Swiss-cheese" type of VSD. 1•2The management strategies, which consist ofmedical, surgical and intervention techniques, depend toa large degree on the size of the VSD.1-4 Approximately40% of VSDs spontaneously and completely closed,with closure rates approaching 80-90% by age 2 years.2Indication ofVSD closure are symptoms of heart failure,left heart chambers overload and history of endocarditis.The surgical approach is considered gold standard butit is associated with morbidity and mortality, high cost,patient discomfort, sternostomy and skin scar.3 Since1988, percutaneous techniques have been conductedin order to reduce those drawbacks of surgery. Morerecently, percutaneous techniques and devices havebeen developed specifically for closure of muscularVSD (m VSD) and perimembranous VSD (pm VSD)using either the Rashkind double umbrella, the BardClamshell, the Button device, theAmplatzer septal, duct118 • Paediatr lrulones, Vol. 50, No. 2, March 2010or muscular VSD occluder, or the Gianturco coils.3AGianturco coils have been widely used to closeunwanted vascular communications and small- tomoderate- sized patent ductus arteriosus, withexcellent closure rates. In 1999, Latiff et al successfullyused this coil to close multiple muscular VSDs in a10-month old boy. Thus, percutaneuos closure ofVSDs using Gianturco coils is a feasible, reasonablealternative to surgery.5'6 We report a case of fouryear-old girl with muscular VSD who underwentcardiac catheterization and transcatheter closure withGianturo coil in Dr. Soetomo Hospital, Surabaya.